Reorganization of Supply Chain Management Function in PERTAMINA EP Based on Newly Developed PERTAMINA EP Business Process - Prahara, Dion Yoske; Saksono, Prasetyo Budi (The Indonesian Journal of Business Administration, 2012)
Supply Chain Management Organization structure implementation in Pertamina EP is not optimal yet in supporting the Supply Chain function’s activities. The existing organization wasn’t good enough in supporting Pertamina EP’s operational activities and supporting continous improvement in strategy and operational activities of Supply Chain. Overlapping and unclear the accountability person caused late in decision making and the accuracy of decision. These can caused lost opportunity in operation, employees demotivation, dan overall will effect the company operational activities.For improvements things mentioned above, the first step is to conduct observation and data collection. The data was analyzed and identified what the potential problems. Potential problems are discussed for the problem solving expectations. After knowing the expectations of the solution,then the new organization structure have to be designed. One of alternative concept is based on Supply Chain Management Business process with accoutability mapping according to business process. By applying the new structure, the problems faced can be overcome Keywords: structure reorganization, supply chain management business process, accountability